2006
DOI: 10.1055/s-2006-942363
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient, Highly Enantioenriched Route to l-Carnitine and α-Lipoic Acid via Hydrolytic Kinetic Resolution

Abstract: A general and practical approach for the synthesis of C-4 chiral building blocks using Jacobsen's hydrolytic kinetic resolution technique to resolve terminal epoxides and diols in high enantiomeric excess and excellent yields is described. The utilization of these building blocks for the synthesis of biologically important natural products L-carnitine and a-lipoic acid is illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Among the advantages of the hydrolytic KR process are its broad applicability over a range of simple as well as functionalized terminal epoxides, high enantioselectivity, remarkable practical appeal, and low catalyst loading. Unsurprisingly, the generality and broad substrate specificity of Jacobsen’s hydrolytic KR methodology has been exploited for the production of a wide range of chiral synthons for natural products and bioactive compounds synthesis, including recent strategies directed towards the synthesis of cytochalasin B,122 apicularen A,123 ( S )‐timolol,124 decarestrictine D,125 cryptocarya diacetate,126 (2 S ,3 R )‐4‐hydroxyornithine,127 (+)‐negamycin,128 (−)‐ cis ‐lauthisan and (+)‐isolaurepan,129 herbarumin III,130 (−)‐deoxoprosopinine,131 ( S )‐atenolol,132 tarchonanthuslactone,133 aspinolide A,134 massoialactone,135 ( R )‐tuberculostearic acid,136 dihydrobenzofurans,137 ( S )‐vigabatrin and ( S )‐dihydrokavain,138 1‐deoxy‐5‐hydroxyshingosine analogues,139 (+)‐patulolide C,140 (+)‐bataxolol,141 (+)‐diplodialides , B and C,142 ( R )‐mexiletine,143 (+)‐allosedamine,144 ( S )‐metoprolol and ( S )‐betaxolol,145 enciprazine,146 and C 13 –C 22 of amphidinolide T2,147 amphidinolide T1,148 iso ‐cladospolide B and cladospolide B,149 anti‐inflammatory agent (7 S ,17 S )‐resolvin D5,150 ( S )‐ and ( R )‐naftopidil,151 neocarazostatin,152 nonactin,153 elecanacin,154 (+)‐peloruside,155 spongiacysteine,156 astrocyte activation suppressor ONO‐2506,157 (−)‐indolizidine 223AB,158 (7 S ,16 R ‐17S)‐resolvin D2,159 (−)‐galantinic acid,160 (+)‐Sch 642305,161 (4 R )‐hydroxy analogues of Annonaceous acetogenins,162 insect pheromones,163 hNK‐1 receptor antagonist,164 L ‐carnitine,165 and (+)‐brefeldin A 166. The use and range of chiral epoxides resolved in these natural or bioactive product syntheses clearly stands as a testament to the true power of Jacobsen’s hydrolytic KR as a routine methodology for stereoselective organic synthesis, as shown in Figure 5.…”
Section: Kinetic Resolution Of Epoxidesmentioning
confidence: 99%
“…Among the advantages of the hydrolytic KR process are its broad applicability over a range of simple as well as functionalized terminal epoxides, high enantioselectivity, remarkable practical appeal, and low catalyst loading. Unsurprisingly, the generality and broad substrate specificity of Jacobsen’s hydrolytic KR methodology has been exploited for the production of a wide range of chiral synthons for natural products and bioactive compounds synthesis, including recent strategies directed towards the synthesis of cytochalasin B,122 apicularen A,123 ( S )‐timolol,124 decarestrictine D,125 cryptocarya diacetate,126 (2 S ,3 R )‐4‐hydroxyornithine,127 (+)‐negamycin,128 (−)‐ cis ‐lauthisan and (+)‐isolaurepan,129 herbarumin III,130 (−)‐deoxoprosopinine,131 ( S )‐atenolol,132 tarchonanthuslactone,133 aspinolide A,134 massoialactone,135 ( R )‐tuberculostearic acid,136 dihydrobenzofurans,137 ( S )‐vigabatrin and ( S )‐dihydrokavain,138 1‐deoxy‐5‐hydroxyshingosine analogues,139 (+)‐patulolide C,140 (+)‐bataxolol,141 (+)‐diplodialides , B and C,142 ( R )‐mexiletine,143 (+)‐allosedamine,144 ( S )‐metoprolol and ( S )‐betaxolol,145 enciprazine,146 and C 13 –C 22 of amphidinolide T2,147 amphidinolide T1,148 iso ‐cladospolide B and cladospolide B,149 anti‐inflammatory agent (7 S ,17 S )‐resolvin D5,150 ( S )‐ and ( R )‐naftopidil,151 neocarazostatin,152 nonactin,153 elecanacin,154 (+)‐peloruside,155 spongiacysteine,156 astrocyte activation suppressor ONO‐2506,157 (−)‐indolizidine 223AB,158 (7 S ,16 R ‐17S)‐resolvin D2,159 (−)‐galantinic acid,160 (+)‐Sch 642305,161 (4 R )‐hydroxy analogues of Annonaceous acetogenins,162 insect pheromones,163 hNK‐1 receptor antagonist,164 L ‐carnitine,165 and (+)‐brefeldin A 166. The use and range of chiral epoxides resolved in these natural or bioactive product syntheses clearly stands as a testament to the true power of Jacobsen’s hydrolytic KR as a routine methodology for stereoselective organic synthesis, as shown in Figure 5.…”
Section: Kinetic Resolution Of Epoxidesmentioning
confidence: 99%
“…Jacobsens hydrolytic kinetic resolution technique using the cobalt chiral salen complex (R,R)- (254) 257), alcohol oxidation and opening of the epoxide with ammonia yields (R)- (6) and N-methylation affords (R)- (7) in high overall yield [184].…”
Section: B-hydroxy-g-amino Acidsmentioning
confidence: 99%
“…Acidic hydrolysis of the cyano group in (R)-461 led to (R)-carnitine 22 in 82% yield as a chloride salt (Scheme 118). 187 More recently, Bose et al 188 reported a practical approach for the synthesis of (R)-GABOB 21 and (R)-carnitine 22 using Jacobsen's hydrolytic kinetic resolution technique to resolve epoxide (±)-474. Thus, treatment of epoxide (±)-474 with (R,R)-salen-Co(III)-OAc 475 complex in water afforded epoxide (R)-474 in 47% yield and 96% ee.…”
Section: Ab-disubstituted C-amino Acidsmentioning
confidence: 99%